RETORISK ANALYSE AF HISTORISKE TEKSTER - Kock, Christian (Temp - tidsskrift for historie, 2014)
ABSTRACT In recent years, rhetoric and the rhetorical tradition have attracted increasing interest from historians, such as Quentin Skinner. The paper aims to explain and illustrate what may be understood by a rhetorical analysis (or “rhetorical criticism”) of historical documents, i.e., how those scholars who identify themselves as rhetoricians tend to define and conduct such an analysis. It is argued that while rhetoricians would sympathize with Skinner’s adoption of speech act theory in his reading of historical documents, they would generally extend their rhetorical readings of such documents to many more features than just the key concepts invoked in them. The paper discusses examples of rhetorical analyses done by prominent contemporary rhetoricians, including Edwin Black, Kenneth Burke, Maurice Charland, and Michael Leff. It relates its view of rhetorical documents to trends in current political theory, and it presents its own brief readings of historically significant speeches by H.P. Hanssen and George W. Bush.